Risk management in information technology outsourcing framework in Malaysia / Syaripah Ruzaini Syed Aris - Syed Aris, Syaripah Ruzaini (2010)
Outsourcing is becoming a trend nowadays. Malaysia also takes this opportunity and embraces in IT outsourcing. As a result, Malaysia has been ranked as the third most attractive destination for outsourcing after India and China. Despite increasing number of organisations that involve in IT outsourcing, it should be noted that IT outsourcing is not a panacea. It requires effective management in order to prevent projects from failing. This problem has also been reported to happen with the IT outsourcing projects in Malaysia. It is essential to identify, manage and mitigate the risk inherent in IT outsourcing projects. Hence, this research would focuses on managing risk in IT outsourcing projects that would be applied in Malaysian environment. There are two research model used in this study. Research Model 1 is to investigate the factors that influenced the practise of risk management in IT outsourcing phase, evaluation on how organisations practised risk management in IT outsourcing project, identification of success rate and relationship between risk management in IT outsourcing phases and IT outsourcing success. Meanwhile, Research Model 2 determines the ranking of risk factors as assessed by managers in Malaysia. There were 38 risk factors used in this study and managers' perception towards those risks was then measured. The new risk factors as envisioned by the managers were also identified. Results from quantitative study revealed that only 35.6% IT outsourcing projects managed to be delivered successfully.